E-064 Technical nd clinical success after venous sinus stenting for treatment of idiopathic intracranial hypertension: initial multi-center experience using a novel guide catheter for access. (23rd July 2022) - Zyck, S; Powers, C; Malik, M; Webb, M; Hawk, H; Birnbaum, L; Mohammed, M; Brinjikji, W; Nimjee, S
Abstract : Introduction: Venous sinus stenting has gained increasing popularity as an alternative to cerebrospinal fluid diversion for the treatment of idiopathic intracranial hypertension (IIH) with associated venous sinus stenosis. We report our initial experience using the TracStar LDP™ (Imperative Care, Campbell, USA, 0.088-inch inner diameter) as the guide catheter to provide access for venous sinus stenting. Methods: A multi-institutional retrospective chart review of a prospectively maintained IRB-approved database was performed. Consecutive patients who underwent venous sinus stenting for IIH between May 2020 and January 2022 were included. Patient characteristics, procedural details, TracStar LDP distal reach, outcomes, and complications were collected and analyzed. Data are presented as mean (standard deviation) and percentage (counts). The paired t-test and was used to determine if there is a significant difference between the gradient pressure across transverse sinus before and after procedure. P value <0.05 was considered to be statistically significant. Results: A total of 58 patients were included in the study. The mean age was 33.8 (10.8) years, and majority of patients were female (93.1%, 54/58). Visual changes prompted evaluation in 86.2% (50/58) of patients and 82.7% (48/58) had papilledema ( Table 1 ). Stent placement was successful in all patients. TracStar LDP catheter was advanced to the location of stent placement in 97.9% (46/47) of cases in which it was attempted. No intermediate catheters were required for access. The large 0.088-inch inner diameter lumen enabled compatibility with all desired stent sizes ranging from 6 to10 millimeters. The superior sagittal sinus was reached in 13.8% (8/58) of patients; the torcula or further distal was reached in 25.9% (15/58) of patients. The transverse sinus or beyond was reached by the TracStar LDP in 74.1% of patients ( Table 1 ). Right-sided sinus stent placement was performed in 74.1% (43/58) of patients. Gradient pressure across transverse sinus stenosis dropped significantly from 19.5 (11.2) mmHg pre-procedure to 1.7 (1.7) mmHg post-stent placement, p<0.001. Clinical improvement was achieved in 87.9% (51/58) of patients. The overall complication rate was 10.3% (6/58), which include two cases of stent re-stenosis, one case of stent thrombosis, one groin hematoma, and two cases that had required further treatment with cerebrospinal fluid diversion at latest follow up. There were no catheter-related complications. Conclusion: The TracStar LDP is a safe and effective access platform for reaching treatment locations in patients who present with idiopathic intracranial hypertension and who are candidates for stent placement. The high rate of technical success in accessing the pathology may be attributed to the unique design of the TracStar LDP. Disclosures: S. Zyck: None. C. Powers: None. M. Malik: None. M. Webb: None. H. Hawk: None. L. Birnbaum: None. M. Mohammed: None. W. Brinjikji: None. S. Nimjee: None.